Kajian Perluasan Lahan Tanaman Tebu Terhadap Berdirinya Pabrik Gula di Lamongan. - Aminuddin, M. Imam (Universitas Islam Darul Ulum, 2016)
Â The current condition of the sugar industry in Indonesia is still of concern in terms of productivity, acreage development aspects as well as the existing social relations. Lamongan is a region of dry land productive potential and enough cultivated sugar cane crops. Data on Department of agriculture Lamongan (2011) shows that the production of sugar cane crop of 13,130 tons (2006), 13,208.62 tonnes (2007), 14,361.52 tonnes (2008), 15,394.5 (2009), ton 17.440.5 ton (2010). This research aims to know the expansion of sugar cane crop land and the response of the community towards the establishment of a sugar factory in Lamongan. This research aims to know the expansion of sugar cane crop land and the response of the community towards the establishment of a sugar factory in Lamongan. Methods used i.e. land analysis (soil pH) in the form of factorial using shelves, the now method, observation and interviews with community leaders and methods of documentation. The data obtained will be analyzed in qualitative diskriptip. Result: 1) Plan the establishment of a sugar factory at Mantup in 2014 has a production capacity of 10,000 TCD (Tons of Cain Day). The required land around 15,000 ha while the land already planted with sugarcane 2,551.73 ha then still need to sugar cane land extension of 12,448.27 ha; 2) based on the analysis of soil that are somewhat the acidic pH of the soil up to approaching neutral, so it is suitable for the growth and development of the sugar cane plant. 3) most of the community strongly supports the establishment of a sugar factory in Mantup, Lamongan. 4) economically, the expansion of the sugar cane plant impacted less profitable for farmers especially had a narrow land and small capital.